Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1088/0963-0252/20/4/045007
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electrons in dual-frequency capacitive radio frequency discharges

Abstract: Two fundamentally different types of dual-frequency (DF) capacitively coupled radio frequency discharges can be used for plasma processing applications to realize separate control of the ion mean energy, E i , and the ion flux, i , at the substrate surface: (i) classical discharges operated at substantially different frequencies, where the low-and high-frequency voltage amplitudes, φ lf and φ hf , are used to control E i and i , respectively; (ii) electrically asymmetric (EA) discharges operated at a fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
157
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(161 citation statements)
references
References 69 publications
1
157
2
1
Order By: Relevance
“…A topic of particular importance in such plasma sources is the role played by surface interaction probabilities in determining the overall discharge dynamics and the electron heating. Voltage waveform tailoring has previously been predicted to be a more effective method of controlling the ion flux and ion bombardment energy than conventional dual frequency approaches in cases where the secondary electron emission probability at the electrodes is high and electron heating can be dominated by secondary electrons emitted from the electrodes [53]. Furthermore, there have been a number of investigations detailing the importance of secondary electron emission coefficients in such plasma sources and the problems and opportunities presented for plasma processing applications by their variation from material to material [54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…A topic of particular importance in such plasma sources is the role played by surface interaction probabilities in determining the overall discharge dynamics and the electron heating. Voltage waveform tailoring has previously been predicted to be a more effective method of controlling the ion flux and ion bombardment energy than conventional dual frequency approaches in cases where the secondary electron emission probability at the electrodes is high and electron heating can be dominated by secondary electrons emitted from the electrodes [53]. Furthermore, there have been a number of investigations detailing the importance of secondary electron emission coefficients in such plasma sources and the problems and opportunities presented for plasma processing applications by their variation from material to material [54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…In such discharges <E i > is controlled by the low-frequency voltage amplitude (by varying the mean sheath voltage), while Г i is adjusted by the high-frequency voltage amplitude (due to the enhanced electron heating at high frequencies). However, a coupling effect of the driving frequencies was found to reduce the quality of the separate control of ion properties [46][47][48][49], which is further limited by the effect of secondary electrons [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…5 However, investigations have shown that the separate control of electron density and ion energy is limited due to the coupling of both frequencies and the effect of secondary electrons by Turner and Chabert, Booth et al, Schulze et al, and so on. [4][5][6][7][8][9] Recently, a novel concept that a discharge is driven by multiple consecutive harmonics was proposed based on the Electrical Asymmetry Effect to solve the problem. [10][11][12] In order to understand the physical and chemical processes of fluorocarbon plasmas, both experimental and theoretical studies have been done over the past few decades.…”
Section: Introductionmentioning
confidence: 99%